2017
DOI: 10.1017/rdc.2017.98
|View full text |Cite
|
Sign up to set email alerts
|

Size Matters: Radiocarbon Dates of <200 µg Ancient Collagen Samples with AixMICADAS and Its Gas Ion Source

Abstract: For many of archaeology’s rarest and most enigmatic bone artifacts (e.g. human remains, bone ornaments, worked bone), the destruction of the 500 mg material necessary for direct accelerator mass spectrometry (AMS) dating on graphite targets would cause irreparable damage; therefore many have not been directly dated. The recently improved gas ion source of the MICADAS (MIni CArbon DAting System) offers a solution to this problem by measuring gaseous samples of 5–100 µg carbon at a level of precision not previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 45 publications
0
26
0
Order By: Relevance
“…Detailed work has been performed to suppress contamination effects for both carbonate and organic material and to survey the residual background for samples ranging between 10 and 100 μgC. These developments allow to date material over the full 50-kyr dating range of 14 C and have enabled us to date ancient collagen [20] and analyze atmospheric aerosols [12]. Ongoing work on dating different fractions of aerosols, purified organic compounds and 14 C formed in situ will incite us to perform more tests with the closed ampoule cracker.…”
Section: Resultsmentioning
confidence: 99%
“…Detailed work has been performed to suppress contamination effects for both carbonate and organic material and to survey the residual background for samples ranging between 10 and 100 μgC. These developments allow to date material over the full 50-kyr dating range of 14 C and have enabled us to date ancient collagen [20] and analyze atmospheric aerosols [12]. Ongoing work on dating different fractions of aerosols, purified organic compounds and 14 C formed in situ will incite us to perform more tests with the closed ampoule cracker.…”
Section: Resultsmentioning
confidence: 99%
“…The automated system reduces both sample preparation time and the risk of contamination through handling, and has been successfully utilised in environmental and climatic applications 23,2528 . In our preliminary study 29 we demonstrated that the gas ion source of the AixMICADAS 30 is suitable for dating bone collagen CO 2 samples of <100 μg C back to 35,000 BP (uncalibrated radiocarbon years before AD 1950).…”
Section: Introductionmentioning
confidence: 97%
“…The aim of this study was to determine a suitable method to pretreat <100 mg bone material and further investigate if the gas ion source of the AixMICADAS 29,30 at CEREGE (Centre de Recherche et d’Enseignement de Geosciences de l’Environnement, Aix-en-Provence, France) is suitable for measuring small archaeological bone samples with sufficient accuracy and precision. We investigated the effect of sample size reduction at both the pretreatment and gas measurement stages.…”
Section: Introductionmentioning
confidence: 99%
“…Measurements were performed at either the Saclay laboratory (LMC 14; NA4 and NA3; in the framework the ARTEMIS program, see above) or the Center for Isotope Research in Groningen (CIR; NA6 and NA5), and the two samples from level NA6 were measured with the new Groningen MIni CArbon DAting System (MICADAS: e.g. Fewlass et al 2018). All the conventional ages were calibrated with OxCal (v4.3.2: Bronk Ramsey 2017) using the IntCal13 calibration curve (Reimer et al 2013).…”
Section: Followingmentioning
confidence: 99%